2013
DOI: 10.1007/s00221-013-3785-9
|View full text |Cite
|
Sign up to set email alerts
|

Can perception of aperture passability be improved immediately after practice in actual passage? Dissociation between walking and wheelchair use

Abstract: Perception of the fit between a person's action capabilities and relevant environmental properties (i.e., affordances) is often fine tuned gradually through experience performing a behavior. However, the immediate effect of such practice on the improvement of affordance perception is unclear. The present study was designed to examine whether a critical factor in the immediate effect of such practice is the opportunity to detect very fine differences between possible and impossible behaviors [i.e., high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…Twenty trials of practice squeezing through doorways facilitated recalibration by reducing errors to only 2.4 cm. Practice effects on recalibration have also been observed in participants walking through doorways while holding a bar horizontally and judging whether it is possible to fit through without turning (Yasuda et al, 2014). Although these studies indicate that practice facilitates recalibration, conditions with locomotor experience without practice, as in Stoffregen and colleagues (2009), were not tested.…”
Section: Recalibration and Exploration In Affordances For Fittingmentioning
confidence: 95%
See 3 more Smart Citations
“…Twenty trials of practice squeezing through doorways facilitated recalibration by reducing errors to only 2.4 cm. Practice effects on recalibration have also been observed in participants walking through doorways while holding a bar horizontally and judging whether it is possible to fit through without turning (Yasuda et al, 2014). Although these studies indicate that practice facilitates recalibration, conditions with locomotor experience without practice, as in Stoffregen and colleagues (2009), were not tested.…”
Section: Recalibration and Exploration In Affordances For Fittingmentioning
confidence: 95%
“…This seems unlikely, as participants were unable to recalibrate when participants practiced walking through a single, large opening size but could recalibrate if practice involved doorways that provided information about both success and failure (Yasuda et al, 2014).…”
Section: Recalibration and Exploration In Affordances For Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an explanation is certainly plausible given that experimental findings that have shown that repeated experience perceiving affordances for a given behavior (or repeated practice performing the behavior itself) can be sufficient to bring perceptual boundaries for that behavior into closer correspondence with the behavioral boundary (e.g., Franchak & Adolph, 2014;Franchak, ver der Zalm, & Adolph, 2010;Mark, 1987;Stoffregen, Yang, Giveans, Flanagan, & Bardy, 2009;Yasuda, Wagman, & Higuchi, 2014).…”
mentioning
confidence: 99%